Quality Management in The Organization of The Energy Complex As a Means of Increasing Competitiveness - Tatiana V. DOBRINOVA; Artem A. GOLOVIN; Alexey A. GOLOVIN; Marina A. PARKHOMCHUK; Ksenia A. CHEBOTAREVA (Communications of International Proceedings, 2021)
The article examines the features of quality management in the organization of the energy complex as a means of increasing competitiveness. Currently, the power industry has developed a sustainable approach to improving quality through quality management systems, which entails not only a change in the production process, but also all its components. Such changes are vital for any company, as quality takes into account the constantly changing needs of consumers. The well-being and high competitiveness of energy sector organizations are impossible without a well-established quality management system, since this is a necessary process in a modern, rapidly developing and changing world. One of the fundamental principles of quality management in general, and in the electric power industry in particular, is customer orientation. This process is essential for any enterprise in today's competitive market. The customer's satisfaction depends on the extent to which, in the customer's opinion, the quality satisfies his/her wishes and needs and corresponds to its purpose. Consequently, solving the problems of ensuring the quality and reliability of power supply, electric power companies are solving the problem of meeting the requirements of stakeholders: shareholders, consumers, personnel and society as a whole in a reliable supply of electricity with the required parameters with minimal stress on natural resources. In the course of the study, the main problems of the implementation of the quality management system in the organizations of the energy complex were identified and the ways of their solution were developed.
Keywords: Quality; Competitiveness; Energy Complex; Energy Enterprises